Das Tempo wird erklärt, nicht die Richtung - Karl Aiginger (Wirtschaftsdienst, 2018)
In diesem Jahr werden die US-Ökonomen William D. Nordhaus und Paul M. Romer mit dem Schwedischen Reichsbankpreis für Wirtschaftswissenschaften zu Ehren von Alfred Nobel für ihre bahnbrechende Forschung in den Bereichen Klimawandel und Innovation ausgezeichnet. Ihre Forschung habe zu einem besseren Verständnis von nachhaltigem Wirtschaftswachstum im Zusammenhang mit Klimawandel und technischem Fortschritt beigetragen. Dieser Beitrag würdigt die Forschung von Paul M. Romer. – – The prize honours the ground-breaking theoretical contribution of Paul M. Romer who found that the speed of growth is no longer exogenous but depends on economic forces. The drivers of growth are human capital, ideas and innovation; these differ from conventional goods due to the fact that their effect is not limited by decreasing returns, but rather grows with use. Romer's model, and practically all models of endogenous growth theory, do not differentiate whether technical progress is labour or resource saving - a distinction that makes an important difference in welfare and climate policy. In his policy agenda, Romer proposes creating 'charter cities' to stimulate growth in countries with unstable governments, as in the East Asia example. While this could rapidly reduce poverty, it is important to pay attention to the adaption of imported technologies to local preferences and ownership of the developing regions.
Keywords: F43; O00; O40; 330